2022
DOI: 10.3389/fcvm.2022.767987
|View full text |Cite
|
Sign up to set email alerts
|

Updated Insights on Cardiac and Vascular Risks of Proton Pump Inhibitors: A Real-World Pharmacovigilance Study

Abstract: BackgroundProton pump inhibitors (PPIs) are among the most widely prescribed medications in clinical practice. However, there are also concerns about the potential risks of long-term PPI use. The present study aimed to examine the safety of PPIs and summarize their potential cardiac and vascular risks in a real-world setting.MethodsThis pharmacovigilance study extracted records between January 2015 and December 2019 from the FDA Adverse Event Reporting System (FAERS) database. The association of seven PPI medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…29 , 30 Baxer and colleagues performed a large‐scale case control study to analyse for an association between SSNHL and vaccinations. 21 The odds ratios for vaccination to SSNHL were 0.965 (95% CI, 0.61–1.50) for influenza vaccine, 0.842 (95% CI 0.39–1.62) for tetanus, and 0.454 (95% CI 0.08–1.53) for zoster vaccine, demonstrating no association between these vaccination and the rate of SSNHL. Given the fact that influenza vaccine has been deemed acceptably safe since they have undergone thorough safety evaluations in the form of continued population‐based post‐market surveillance, 31 , 32 we set it as the control group to compare the disproportionality pattern.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…29 , 30 Baxer and colleagues performed a large‐scale case control study to analyse for an association between SSNHL and vaccinations. 21 The odds ratios for vaccination to SSNHL were 0.965 (95% CI, 0.61–1.50) for influenza vaccine, 0.842 (95% CI 0.39–1.62) for tetanus, and 0.454 (95% CI 0.08–1.53) for zoster vaccine, demonstrating no association between these vaccination and the rate of SSNHL. Given the fact that influenza vaccine has been deemed acceptably safe since they have undergone thorough safety evaluations in the form of continued population‐based post‐market surveillance, 31 , 32 we set it as the control group to compare the disproportionality pattern.…”
Section: Discussionmentioning
confidence: 93%
“…Long before COVID‐19 vaccine, anecdotal case reports of SSNHL following other vaccines have led to a speculation that vaccination might be the cause of hearing loss in some cases 29,30 . Baxer and colleagues performed a large‐scale case control study to analyse for an association between SSNHL and vaccinations 21 . The odds ratios for vaccination to SSNHL were 0.965 (95% CI, 0.61–1.50) for influenza vaccine, 0.842 (95% CI 0.39–1.62) for tetanus, and 0.454 (95% CI 0.08–1.53) for zoster vaccine, demonstrating no association between these vaccination and the rate of SSNHL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent of clopidogrel use, Dahal et al [ 41 ] demonstrated that PPI use alone was not at increased risk for cardiovascular mortality, all-cause mortality, myocardial infarction, or stroke in a meta-analysis of nine RCTs including patients taking aspirin for the prevention of cardiovascular diseases and stroke. Zhai et al [ 42 ] sought to examine the safety of PPIs for cardiac and vascular health using the Food and Drug Administration Adverse Event Reporting System (FAERS). PPIs were not associated with more cardiac and vascular events compared with the whole database.…”
Section: Discussionmentioning
confidence: 99%
“…PPIs are also metabolized by CYP enzymes and thus could inhibit the conversion of clopidogrel into its active metabolite ( Furuta et al, 2017 ). Furthermore, mounting clinical data have shown that long-term intake of PPIs increases the susceptibility of patients to serious adverse events, including cardiovascular events and damage to the lower GI tract ( Lue and Lanas, 2016 ; Xie et al, 2019 ; Marlicz et al, 2022 ; Zhai et al, 2022 ). However, the existing clinical studies of the association between cardiovascular events and the concomitant use of PPIs with aspirin-clopidogrel DAPT in CHD have been conflicting ( Ben Ghezala et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%